2009
DOI: 10.1007/s00018-009-0138-8
|View full text |Cite
|
Sign up to set email alerts
|

When a theory of aging ages badly

Abstract: According to the widely acknowledged mitochondrial free radical theory of aging (MFRTA), the macromolecular damage that results from the production of toxic reactive oxygen species (ROS) during cellular respiration is THE cause of aging. However, although it is clear that oxidative damage increases during aging, the fundamental question regarding whether mitochondrial oxidative stress is in any way causal to the aging process remains unresolved. An increasing number of studies on long-lived vertebrate species,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
152
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 227 publications
(159 citation statements)
references
References 73 publications
5
152
1
1
Order By: Relevance
“…From the above we believe it to be reasonable to contend that the MFRTA has been falsified [33]. However, there is no reason to doubt the validity of the observations on which the theory was based, including the data that suggest that ROS toxicity might sometimes be involved in disease progression.…”
Section: Need For An Alternative Point Of Viewmentioning
confidence: 93%
“…From the above we believe it to be reasonable to contend that the MFRTA has been falsified [33]. However, there is no reason to doubt the validity of the observations on which the theory was based, including the data that suggest that ROS toxicity might sometimes be involved in disease progression.…”
Section: Need For An Alternative Point Of Viewmentioning
confidence: 93%
“…Nowadays this theory is matter of debate, since recent mounting evidence revealed that ROS are not simply subproducts of mitochondrial metabolism, but they perform important signaling roles in the healthy cell. In addition, several studies on long-lived vertebrate species, mutants and transgenic animals challenged the old theory (for a review see Lapointe and Hekimi, 2010). Although this new view of the ROS is gathering strength, many studies clearly demonstrate that excessive ROS production is involved in several human pathologies that include mitochondrial diseases and neurodegenerative disorders such as Alzheimer´s and Parkinson´s diseases.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…24 The theory that aging is caused by damage could not be reconciled with observations and experiments. 25,26 It needs to be mentioned that activation of some components of DNA damage response (DDR) without actual Figure 1. the tOr network.…”
Section: Tor and Agingmentioning
confidence: 99%